ANALISIS KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK MTsN SABANG MELALUI IMPLEMENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING - Nafisah Hanim (UIN AR-RANIRY, 2019)
This Research to analyze the abilityof students through the implementation of the Discovery Learning learning model has been carried out at MTsN Sabang. The research design used was a Pre-Experimental Design in the form of a One-Shot Case Study. The population in this study were all students of class VII MTsN Sabang consisting of 4 classes with class VII3 samples collected by 25 students. The research sample was selected by purposive sampling. Data collection was carried out using a written test of 10-question questions. Data were analyzed using a formula that was calculated based on scores obtained from essay tests. The results showed the victory over the assessment of critical indicators obtained a simple assessment of getting a percentage of 76%, indicators of building skills gained 64.8%, indicators were obtained obtaining a percentage of 71.8%, indicators giving explanations received obtaining a percentage of 70.6%, and 71% of strategies. Critical learning about students in the ecosystem material through the implementation of the Discovery Learning learning model in MTsN Sabang is in the high category.